The Influence of Convenience, Benefits, and Security on Consumer Preferences in Adopting QRIS Non-Cash Payments - Syahrin, Khalfi; Arisandy, Yosy; Handika, Yuli (Airlangga Journal of Innovation Management, 2025)
This study aims to determine the influence of convenience, Benefits, and security on consumer preferences in using QRIS as a non-cash payment system. This study uses a quantitative approach with a purposive sampling technique, namely a sampling method based on certain considerations or criteria relevant to the research objectives so that the selected respondents truly match the required characteristics. The number of respondents in this study was 100 people who had met these criteria. Data collection was carried out through an online questionnaire, while data analysis included validity, reliability, normality, multicollinearity tests, T-tests, F-tests, and coefficients of determination processed using SPSS version 2025. The results of the study indicate that ease, Benefits, and security each have a positive and significant effect on consumer preferences in using QRIS. The easier QRIS is to operate, the more consumers are interested in adopting it. Likewise, the greater the perceived benefits, the stronger the tendency for consumers to prefer QRIS as a payment method. In addition, a secure system fosters greater consumer trust, thereby increasing the likelihood of usage. Collectively, these three factors ease, Benefits, and security interact to enhance consumer interest and decision-making in adopting QRIS. The practical implication of these findings is that service providers and policymakers should prioritize the continuous improvement of system usability, perceived benefits, and security features to strengthen consumer trust and encourage wider adoption of QRIS in daily transactions